2009
DOI: 10.1016/j.foodchem.2009.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipids and their contribution to the taste of migaki-nishin (dried herring fillet) during drying

Abstract: This study was conducted to investigate the changes in lipids and their effect on the taste of migaki-nishin during drying. Lipid was extracted from herring fillets on different drying stages to measure the degree of lipid oxidation and changes in lipid composition, and fatty acid profile. Peroxide value, carbonyl value and acid value of the lipids were significantly increased (P < 0.05) during the drying period. Marked increase in free fatty acids, with decreases in triglyceride and phospholipid content were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 25 publications
(16 reference statements)
7
17
0
Order By: Relevance
“…Packaging methods (open, sealed and vacuum) did not have significant effects on PL hydrolysis (Fig. 2a-c), supporting the explanation that PL hydrolytic processes were largely driven by enzymatic activities (Chaijan et al 2006;Shah et al 2009). …”
Section: Lipid Hydrolysissupporting
confidence: 71%
See 1 more Smart Citation
“…Packaging methods (open, sealed and vacuum) did not have significant effects on PL hydrolysis (Fig. 2a-c), supporting the explanation that PL hydrolytic processes were largely driven by enzymatic activities (Chaijan et al 2006;Shah et al 2009). …”
Section: Lipid Hydrolysissupporting
confidence: 71%
“…This as discussed in Sect. 3.3 could be explained by differences in phospholipids proportion (Shah et al 2009). …”
Section: Fatty Acids (Fa) Compositionmentioning
confidence: 99%
“…Total lipids were extracted from the soy sauce samples with a solvent mixture of chloroform:methanol:distilled water (10:5:3, v/v/v) according to the method of Azad Shah et al. (). The extracts were dried under vacuum on a rotary evaporator and finished with a nitrogen flow.…”
Section: Methodsmentioning
confidence: 99%
“…The evolution of lipids, which participate in aroma development, has been concerned in several fermented soya products, such as natto, Japanese miso, Indonesian temp, and Chinese soy sauce (de Reu, Ramdaras, Rombouts, & Nout, ; Feng et al., ; Kiuchi, Ohta, Itoh, Takabayashi, & Ebine, ; Shieh, Beuchat, Worthington, & Phillips, ; Visessanguan et al., ). Meanwhile, Azad Shah, Tokunaga, Kurihara, and Takahashi () reported that lipolysis and lipid oxidation are responsible for the thickness, mouthfulness, and continuity taste in migaki‐nishin, a dried fish product. To date, published studies have focused on proteins (Chou & Ling, ; Kaewkrod, Niamsiri, Likitwattanasade, & Lertsiri, ; Yong & Wood, ) and starch (Elfalleh, Sun, He, Kong, & Ma, ; Liu, Chen, Fan, Huang, & Han, ) degradation and umami peptides (Kim et al., ; Zhuang et al., ) of soy sauce.…”
Section: Introductionmentioning
confidence: 99%
“…Leticia, Paola, Jordi, Julio, & Sancho, 2017;Zhang et al, 2017), showing that natural plant extract could decrease the lipid oxidation of meat.Lipid oxidation, corresponding to the oxidative deterioration of polyunsaturated fatty acids in fish muscle, leads to the production of off-flavor, thereby reducing the quality of food(Azad Shah et al, 2009). With respect to volatile compounds of salted fish, lipid oxidation might somewhat affect the formulation of volatile compounds.…”
mentioning
confidence: 99%